LINGUODIDACTIC ROLE OF PROVERBS IN LANGUAGE TEACHING PROCESS - Mukhammadiyeva, Madinabonu (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The article analyzes the significant relevance of proverbs within paremiology and applied linguistics, as proverbs embody linguistic creativity, cultural values, and socio-pragmatic norms The relevance of this research lies in its focus on the didactic potential of proverbs as multifunctional tools that enrich foreign language education by enhancing learners’ linguistic proficiency, cultural fluency, and socio-pragmatic awareness. The article shows novelty of the research which is defined by its interdisciplinary approach, which synthesizes linguistic, cultural, pragmatic, and didactic perspectives while applying phraseodidactic principles. A comparative analysis of English and Uzbek proverbs reveals the parallels and divergences in their origins, structures, and communicative functions, demonstrating their methodological significance for modern, pragmatically oriented stylistics. Moreover, the study situates proverbs within authentic discourse, showing how traditional forms evolve into anti-proverbs and adapt to contemporary communicative needs. The research results show that proverbs play a crucial role in developing learners’ semiotic, discursive, socio-pragmatic, and ethno-sociocultural micro-skills. Empirical findings confirm that their effective integration into teaching practice enhances learners’ comprehension of figurative language, improves idiomatic competence, and fosters cultural sensitivity. The study concludes that proverbs are best introduced at advanced proficiency levels through authentic materials such as literature, media, and popular culture, which not only strengthen linguistic accuracy but also promote intercultural awareness and critical thinking. Thus, the article underscores the value of paremiology as a bridge between language pedagogy and cultural education, offering practical insights for curriculum design and communicative language teaching.
Keywords: paremiology; proverbs; intangible cultural heritage; sociopragmatic competence; intercultural communication; phraseodidactics; language acquisition; cultural values; pragmatic functions; authentic contexts; B2 proficiency level; educational curriculum